Standardization of Vegan Yoghurt from Coconut and Soya Bean Milk Enriched with Watermelon Juice - Kalavathi, M; Madhavi, D; Sireesha, G (Journal of Postharvest Technology, 2022)
The research in recent times is mostly focused on plant-based or non-dairy milk substitutes. The  issue of insufficient dairy milk supply, dairy milk allergy, or lactose intolerance is increasing the  preference for vegan milk or dairy milk alternatives. Due to the health benefits and nutritional value  of soybean milk, coconut milk, and sesame milk, they are the perfect substitutes for dairy milk.  Soaked and blended coconut and soybeans were filtered through muslin cloth to extract the milk.  The extracted milks were used in different proportions to develop and standardize samples (S) of  plant-based vegan yogurt. 1% lactic acid bacteria was used for fermentation, namely, S1 - coconut  milk and soy milk yogurt (50%:50%), S2 - coconut milk and soy milk yogurt (75%:25%), S3 - coconut  milk and soy milk yogurt (75%:25%), S4 - coconut milk and soy milk yogurt with watermelon juice  (50%:40%:10%), and S5 - coconut milk and soy milk yogurt with watermelon juice (50%:30%:20%).  The duration of the fermentation process and the quality of the fermented milk were tested, and  the pH was recorded at different time periods. Nutritional quality and organoleptic properties were  analyzed. The results showed that the most acceptable yogurt was sample S4 - coconut and soy  milk yogurt with watermelon juice (50%:40%:10%). The results also showed that the developed  value-added plant-based yogurt had superior nutritional and sensory attributes compared to  conventional yogurt. Plant-based yogurt is the best option for vegans as a replacement for dairy  yogurt and to prevent malnutrition.
Keywords: Dairy milk; vegan yogurt; soybean milk; coconut milk; watermelon juice